2017
DOI: 10.2131/jts.42.85
|View full text |Cite
|
Sign up to set email alerts
|

Selenium uptake through cystine transporter mediated by glutathione conjugation

Abstract: -Selenium (Se) is an essential trace element and is regarded as a protective agent against cancer. In particular, antioxidant effects of selenoenzymes contribute to cancer prevention. Se can also produce reactive oxygen species and, thereby, exert cancer-selective cytotoxicity. Selenodiglutathione (SDG) is a primary Se metabolite conjugated to two glutathione (GSH) moieties. SDG increases intracellular Se accumulation and is more toxic than selenous acid (H 2 SeO 3 ), but the mechanisms for importing Se compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…As selenium is also transported by xCT [23,43], we hypothesized that selenium compounds are able to impair cysteine uptake. Albeit having antioxidant properties, selenium can also function as a pro-oxidant and exhibit toxicity toward tumor cells [40,42]. In the present study, we focused on the selenium–chrysin (SeChry) compound [42,48], which was described as having anti-tumor effects, even without selenium [42,48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As selenium is also transported by xCT [23,43], we hypothesized that selenium compounds are able to impair cysteine uptake. Albeit having antioxidant properties, selenium can also function as a pro-oxidant and exhibit toxicity toward tumor cells [40,42]. In the present study, we focused on the selenium–chrysin (SeChry) compound [42,48], which was described as having anti-tumor effects, even without selenium [42,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium (Se) is an essential element required for the maintenance of cellular redox balance [40,41] by being a cofactor of mammalian enzymes such as glutathione peroxidase [40,42]. In addition, selenium compounds are taken up by cyst(e)ine transporters [40,43,44], and some studies demonstrated that selenium itself exerts anti-tumoral activity [45,46]. In accordance, in small-cell lung cancer cell lines, xCT activity was related to higher selenium salt (selenite) sensitivity [47], revealing the possible use of xCT as a mediator of therapies based on selenium.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting compound, selenodicysteine (CSSeSC), is taken into the cell by xCT. 17) In the cell, CSSeSC undergoes sequential metabolisms into hydrogen selenide (H 2 Se) by GSH and finally oxidizes to elemental Se, accompanied with ROS generation. 21) This oxidative stress induces protective cellular responses, including xCT upregulation, as observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently identified evidence that GSSeSG enters into cells more rapidly than selenite through an amino acid transporter xCT. 17) xCT is coded on the SLC7A11 gene and constitutes the cystine/glutamate exchange system x c -that supplies cysteine necessary for GSH biosynthesis. 18) Cells increase GSH synthesis by upregulating xCT expression to cope with reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Gentamicin C1a is considered as a precursor to the synthesis of etimicin (Wei et al, 2019). Selenodiglutathione is a primary Se metabolite conjugated to two glutathione moieties, and it increase intracellular Se accumulation and is more toxic than selenous acid (Fisher et al, 2016;Tobe et al, 2017). L-arabinose, a kind of plant-specific five-carbon aldose, is a naturally occurring constituent of plant polysaccharides, and often extracted from vegetable gum, corn straw or beet (Feher, Gal, Feher, Barta, & Reczey, 2015;Kotake, Yamanashi, Imaizumi, & Tsumuraya, 2016;Moremi, Jansen Van Rensburg, & La Grange, 2020).…”
Section: Discussionmentioning
confidence: 99%